BATAS EPISTEMOLOGIS SAINS DALAM PENAFSIRAN AL-QUR'AN: Tinjauan Kritis atas Praktik Pseudosains dalam Tafsir Ilmi - Rizki Rahmadani; Lasmiati Radiah; Taufik Warman Mahfudz (JURNAL ILMIAH NUSANTARA, 2026)
The integration between empirical science and the interpretation of the Qur'an has become one of the most dynamic issues in the study of contemporary interpretation. This tendency commonly called scientific interpretation, on the one hand, opens up a constructive dialogue between revelation and scientific knowledge, but on the other hand has the potential to give birth to pseudoscientific claims that appear to be superficial scientific but do not have a solid methodological foundation. This research investigates the epistemological boundaries that should govern the relationship between science and interpretation, as well as mapping the variety of pseudoscientific practices found in the tradition of interpretation. Using a qualitative-descriptive literature study approach, this study concludes that the contribution of science in interpretation should be limited to the function of illustration and confirmation, not as an authority to determine the meaning of the text. Various patterns of pseudoscience that have been successfully identified include excessive retrofitting of interpretations, the use of outdated scientific theories, the exploitation of numerical ambiguity, and the presentation of anecdotal evidence as if it represents scientific consensus. These findings confirm the need for a robust epistemological framework to maintain the integrity of interpretation while preventing distortions of religious understanding.